THE URGENCY OF DEMOCRATIC ETHICS IN SHAPING NATIONAL INTEGRATION: URGENSI ETIKA DEMOKRASI DALAM MEMBENTUK INTEGRASI NASIONAL - Fifi Zuhriah; Heru Ismaya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Ethics are guidelines and orientations in decision-making, activities, and human actions in undergoing democracy. The implementation of democratic values in the life of the nation and state is certainly not free from violations related to violations of democratic values. Violations of democratic values are acts of discrimination against certain individuals (human rights violations). This reflects that society has not yet realized democratic values in its life. National integration is a way out to deal with various conflicts. National integration as an Indonesian cultural strategy basically unites the vision and mission between a number of interests and identities of each member of society with a complex cultural background. By upholding the principles of ethics in the application of democracy. This research is a literature analysis research, which is qualitative in nature. Qualitative field research conducted by researchers to examine a reference to study and analyze the urgency of democratic ethics in forming national integration. So this research is This research is descriptive qualitative.